The effects of electronic word of mouth (e-WOM) on tourists’ decisions to visit the Magetan Refugia Garden (indigenous tree flora) in the COVID-19 pandemic era - Vania Dwike Hapsari; Erlyna Wida Riptanti; Isti Khomah (Tourism)
The internet of things (IoT) era has seen the flow of information evolving from word of mouth (WOM) to electronic word of mouth (e-WOM). One example of e-WOM’s role in the tourism sector is agrotourism in the Magetan Refugia Garden (MRG) in Indonesia. The purpose of establishing this agrotourism site is to control pests in the area, but which has both agricultural and tourism functions. Since the COVID-19 pandemic has lessened the number of visitors, a strategy to enhance the number of visits is required. This study aims to figure out how e-WOM influences visitors’ decisions to come. A basic descriptive-analytical approach was employed in conjunction with a survey technique, with a purposive sampling method utilized to gather the research sample (a total of 140 respondents). The results of the questionnaire were checked using structural equation modeling-partial least squares (SEM-PLS). The findings have revealed that e-WOM has a negligible direct effect on the decision to visit this tourist destination. It is assumed that other factors therefore influence shifts in behavior due to the COVID-19 epidemic, such as uncertain public health and finances which have a negative impact on the number of tourists visiting the Magetan Refugia Garden.